A comparative study of ropivacaine 0.75% and bupivacaine 0.5% for segmental epidural anaesthesia in patients undergoing percutaneous nephrolithotomy - Ganvir, Mayur S.; Patkar, Geeta A.; Parikh, Devangi A.; Tendolkar, Bharati A. (International Journal of Research in Medical Sciences, 2017)
Background: Percutaneous nephrolithotomy (PCNL) is used for fragmentation and removal of stones from pelvicalyceal system using a nephroscope passed into the kidneys through a track created in the patients back. PCNL is the treatment of choice for larger renal stones of size more than 20 to 30 mm, staghorn stones and stones that are multiple or resistant to extra corporeal shock. Methods: This prospective, randomized, open, controlled trial was carried out in 60 adult patients undergoing elective surgical procedure. The patients were randomly divided into two groups of 30 each. Each group underwent PCNL under segmental epidural. Results: Both the groups were comparable with respect to their demographic data, duration of surgery, size of stone and baseline vital parameters. Nine patients in Ropivacaine group and seven patients in Bupivacaine group developed clinically significant hypotension. The incidence of complications was similar in both the group. The fall in haemoglobin was similar in both the groups and none of the patients required blood transfusion. Conclusions: Segmental epidural anaesthesia is a safe alternative technique to general anesthesia for PCNL. Both the drugs ropivacine and bupivacaine were safe and clinically comparable in segmental epidural for PCNL.